Comparison of transperitoneal and retroperitoneal laparoscopic nephrectomy for renal cell carcinoma: a systematic review and meta‐analysis. (29th October 2012) - Fan, Xinxiang; Xu, Kewei; Lin, Tianxin; Liu, Hao; Yin, Zi; Dong, Wen; Huang, Hai; Huang, Jian
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Laparoscopic nephrectomy is now considered to be the reference procedure for kidney cancer. It can be performed via a transperitoneal or retroperitoneal approach. Each approach has its advantages and disadvantages. No definitive conclusions regarding objective difference between the two approaches have been reached to date. This meta‐analysis indicates that in appropriately selected patients, especially patients with posteriorly located renal tumors, the retroperitoneal approach may be faster and equally safe compared with the transperitoneal approach. Objective To evaluate the efficiency and safety of the retroperitoneal and transperitoneal approaches in laparoscopic radical/partial nephrectomy (RN/PN) for renal cell carcinoma. Methods A systematic search of PUBMED, EMBASE, and the Cochrane Library was performed to identify prospective randomized controlled trials and retrospective observational studies that compared the outcomes of the two approaches. Outcomes of interest included perioperative and postoperative variables, surgical complications and oncological variables. Results Twelve studies assessing transperitoneal laparoscopic RN (TLRN) vs retroperitoneal laparoscopic RN (RLRN) and six studies assessing transperitoneal laparoscopic PN (TLPN) vs retroperitoneal laparoscopic PN (RLPN) were included. The RLRN approach had a shorter time to renal artery control (weighted mean difference [WMD] 68.65 min; 95% confidence interval [CI] 40.80–96.50; P < 0.001) and a lower overall complication rate (odds ratio 2.12; 95% CI 1.30–3.47; P = 0.003) than TLRN. RLPN had a shorter operating time (WMD 48.85 min; 95% CI 29.33–68.37; P < 0.001) and a shorter length of hospital stay (WMD 1.01 days; 95% CI 0.39–1.63; P = 0.001) than TLPN. There were no significant differences between the retroperitoneal and transperitoneal approaches in other outcomes of interest. Conclusions This meta‐analysis indicates that, in appropriately selected patients, especially patients with posteriorly located renal tumours, the retroperitoneal approach may be faster and equally safe compared with the transperitoneal approach. Despite our rigorous methodology, conclusions drawn from our pooled results should be interpreted with caution because of the inherent limitations of the included studies.